How much do technological gap, firm size, and regional characteristics matter for the absorptive capacity of Italian enterprises? - Cesare Imbriani; Rosanna Pittiglio; Filippo Reganati; Edgardo Sica (FIW - Research Centre International Economics, 2011)
The absorptive capacity represents the ability of enterprises to efficiently absorb and internalise knowledge from outside: it represents the link between firms' capabilities to implement new products and the external stock of technological opportunities, such as those spilled-out from Multinational Enterprises (MNEs). In this framework, the present paper aims at testing the absorptive capacity of Italian firms arising from inward Foreign Direct Investment (FDI). Given the peculiar characteristics of the Italian productive system, our analysis will focus on three different dimensions: technology gap between foreign and local enterprises, domestic firm size, and geographical distribution of firms. Our findings suggest that technological gap and firm size matter considerably for the spillover effect. Moreover, spillovers exhibit a subnational dimension, being present only in North-East region of the Peninsula.
Keywords: L33; F23; O17; 330; absorptive capacity; MNEs; FDI spillovers; technology gap; firm size; regionality